Performance enhancement of parallel‐operated inverter‐based virtual synchronous generators supplying active load - Rahimi, Mohsen; Momenzadeh, Morteza; Akhbari, Allahyar; Khooban, Mohammad Hassan (IET electric power applications, 2023)
Inverter‐based virtual synchronous generators (VSGs) by introducing the virtual inertia enhance the microgrid frequency stability. The subject of this paper is regarding the stability analysis and enhancement of the study system comprising parallel‐operated VSGs feeding an active load. The active load with tightly closed‐loop control behaves such as constant power load resulting in stability issue. In the article, impacts of the dc‐side voltage control bandwidth of the active load and power level of active load on the system stability are examined. Then, an approach based on feedback linearising technique implemented on VSGs is presented for stabilising the system at higher levels of active load power. By employing the presented approach, the VSGs show reduced output impedance at the low and middle‐frequency ranges, and this in turn stabilises the system even at the rated level of the active load power and at higher control bandwidths of the active load dc‐side voltage control loop. Next, the linearised state‐space equations of converters and related controllers are transferred from local dq‐reference frames to a common dq‐reference frame, and then stability of the whole study system is analytically examined. At the end, time‐domain simulations and hardware‐in‐the‐loop experiments are given to verify the analytical results. The subject of this paper is regarding the stability analysis and enhancement of the study system comprising parallel‐operated VSGs feeding an active load.